Compilación fotográfica del Centro Histórico de Latacunga - Altamirano Pacheco, Juan Sebastián (2016)
The principle purpose which leads me to propose this topic, and addressed the Historic Center of Latacunga, is that through photography allows us to know the beauty of our city and this compilation and simple description of monuments, houses and parks are known and admired by the people who visit this latacungeño place, and tourists who come to Latacunga has a wonderful impression for the places that they visited. The historic center is considered Cultural Heritage of the State from May 25, 1982, where he was recognized for the wealth it has, however we should take advantage of the tourist and historic resource as the House of the Marquises, the church of the Merced, church and Plaza de Santo Domingo, Vicente Leon school, the Civil Hospital Hermanas Paez and Filantropia Park , church and square of San Agustin, the University of the Armed Forces, Isidro Ayora Museum, San Francisco, City Hall, the Cathedral Church and Vicente Leon Park. Latacunga, located in the center of the country, possessed of a colonial and republican architecture of special features, rich in history, tradition and culture that attract the attention of all its inhabitants, it has a full historical center of attractions that gladness who visits this city. Small streets and houses built with pumice stone and roof tile make this place a privileged site worthy of admiration for locals and foreigners.